Studies on the technology of suspension fermentation of tea leaf homogenates - XIA Tao; TONG Qi-qing; XIAO Wei-xiang (浙江大学学报. 农业与生命科学版, 2000)
Variation and technological regulation of suspension fermentation of tea leaf homogenates were investigated. The results showed that although the activity of polyphenol oxidase was obviously inhibited during fermenting process, it could fulfill the enzymatic oxidation. Some significant correlations were found between the changes of technologic testing parameters such as oxido-reducing potential (ORP), dissolved oxygen (DO) concentration, oxygen uptake rate (OUR), total color (TC) and the consumption of substrates and the formation of oxidative product theaflavins (TFs) in fermentation system. The increase of oxygen supply and the addition of organic ester A could promote TFs formation. The major cause to limit the fermentation was the insufficient oxygen supply under high suspension concentration. The oxygen supply and the quality of black tea involved could be improved by using the pitch-fed fermentation method.